Social Networking of Owner-Managers in Small Accommodation in Malaysia: Implications for HRD - Victoria, Jonathan (UNIMAS Publisher, 2018)
Small accommodation providers are challenged to grow their business due to their limited resources. Although social networking is suggested to assist organization growth, few studies have focused on how owner-managers in the Malaysian hospitality industry network and the value they attach to it. This paper presents findings of 10 in-depth interviews of social networking motivation and barrier of owner-managers of small accommodation in Kuching, Malaysia. The findings show that the owner-managers were motivated by the perceived organizational and personal benefits of networking with others. However, issues such as social competence and business concerns were identified as barriers that may limit their participation in networking. To overcome these issues, it is suggested that educators, policymakers, and trade associations work together with the owner-managers to address their specific development and resource needs.